2019
DOI: 10.12693/aphyspola.135.232
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Methods on the Corrosion Resistance of 304 Stainless Steel Joints

Abstract: This paper describes the study of corrosion resistance of 304 stainless steel joint welded with different heat input in the material. The welding was done with classic methods and their low energy varieties. The structure and properties of austenitic steels joints strongly depend on the level of heat input in the material. Electrochemical corrosion resistance tests were carried out in 5% NaCl solution. The obtained results show the decrease of corrosion resistance of tested joints in comparison to the base mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Nickel and its alloys are now thoroughly investigated in relation to many aspects and application areas [ [19] , [20] , [21] ], including brazing [ 22 ], the welding of structural elements operating in extreme heat conditions and harsh environments [ 23 ], the welding of nickel based alloys with unalloyed steels, the structural analysis of welded joints [ 24 ], the joining of bimetallic materials with Ni-based alloy-plated layers [ [25] , [26] ], the laser welding of finned tubes with superalloy Inconel 625 [ 27 ] and the making of surface alloys using thermal spraying or welding-based techniques [ 28 , 29 ]. However, information concerning the welding of thin sheets made of Inconel type alloys is presented in scientific publications to a rather narrow extent [ [30] , [31] , [32] ]. The aforesaid situation inspired investigation related to the welding of 1 mm thick sheets made of superalloy Inconel 718, formed using cold working and interoperative recrystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel and its alloys are now thoroughly investigated in relation to many aspects and application areas [ [19] , [20] , [21] ], including brazing [ 22 ], the welding of structural elements operating in extreme heat conditions and harsh environments [ 23 ], the welding of nickel based alloys with unalloyed steels, the structural analysis of welded joints [ 24 ], the joining of bimetallic materials with Ni-based alloy-plated layers [ [25] , [26] ], the laser welding of finned tubes with superalloy Inconel 625 [ 27 ] and the making of surface alloys using thermal spraying or welding-based techniques [ 28 , 29 ]. However, information concerning the welding of thin sheets made of Inconel type alloys is presented in scientific publications to a rather narrow extent [ [30] , [31] , [32] ]. The aforesaid situation inspired investigation related to the welding of 1 mm thick sheets made of superalloy Inconel 718, formed using cold working and interoperative recrystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, under low heat input and low cooling rates, the welded joint exhibited high corrosion resistance and limited electrochemical reactions. Gucwa et al 16 analyzed the corrosion resistance of SS304 welded joints under different material heat input. It was found that the microstructure and properties of austenitic stainless steel joints are largely dependent on the heat input of the weld material, and the corrosion resistance of the welded joints is worse than that of the base material.…”
Section: Introductionmentioning
confidence: 99%
“…Radhamani et al found that due to the influence of martensite and retained austenite in the metal, the hydrogen content is relatively high in the weld zone and heat-affected zone of steel, which easily leads to brittle fractures at the metal's edge (Radhamani et al, 2020). Gucwa et al also showed that when the cathodic polarization potential increased from -1,050 mV to -850 mV, the hydrogen embrittlement of low-alloy steel decreased significantly (Gucwa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%